Classification, Symptoms, Treatment and Preventive Strategies of Diabetes. A guide to the basic - Magda Madoń; Patrycja Proszowska; Daria Sieniawska; Adrianna Orzeł; Aleksandra Pich-Czekierda; Zuzanna Kotowicz; Julia Sieniawska (Kazimierz Wielki University, 2024)
Introduction Diabetes is a chronic metabolic disorder characterized by impaired insulin secretion and action. Risk factors for diabetes include age, obesity, low physical activity, hypertension, lipid disorders, and genetic predisposition. Symptoms of diabetes typically include frequent urination, weight loss, excessive thirst, weakness, fatigue, susceptibility to fungal infections and recurrent boils. Diabetes is a prevalent and significant societal concern, often causing anxiety, uncertainty and a sense of danger upon diagnosis. Aim of the study The aim of the study is to provide a comprehensive analysis of diabetes, including its classification, characteristic symptoms, the most frequently occurring diabetes-related complications, and preventive strategies. Through a detailed discussion of these issues, our goal is to increase public awareness of diabetes and provide readers with comprehensive knowledge about this disease. Material and method This article presents the current state of knowledge about diabetes. A literature review was conducted using the PubMed, Google Scholar and Web of Science databases, utilizing keywords such as "diabetes", "diabetes mellitus", "diabetes complications". Results The number of people with diabetes has continued to rise. Scientists predict that in a few decades, this number could reach more than half a billion globally. Many individuals may not realize that they are at risk for this civilization disease, often due to unhealthy lifestyle choices such as smoking, obesity, and lack of physical activity. Early initiation of treatment is crucial in preventing serious complications. Despite living with diabetes for years, some patients still report insufficient knowledge about their condition. Therefore, educating patients about the nature of the disease and its treatment is essential for improving their quality of life.